2013
DOI: 10.1097/aln.0b013e318291c165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Positive End-expiratory Pressure on Regional Ventilation Distribution during Mechanical Ventilation after Surfactant Depletion

Abstract: Ventilation of poorly aerated dependent lung regions, which can promote the local concentration of mechanical stresses, was the predominant functional behavior in surfactant-depleted lung. Potential tidal recruitment of atelectatic lung regions involved a smaller fraction of the imaged lung. Significant ventilation redistribution to aerated lung regions places these at risk of increased stretch injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…This difference is unlikely to affect the lung volume estimates in a normal lungs, however may gain importance after lung lavage where the airway closures may lead to trapped air in the lung periphery. Using a similar experimental model where the regional lung ventilation was assessed by synchrotron imaging, we recently demonstrated that air trapping may be encountered at PEEP level of 3 cmH 2 O [17]. Considering that the maximum amount of such lung regions with trapped air does not exceed 10%, the impact of this phenomenon on our results is minor.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…This difference is unlikely to affect the lung volume estimates in a normal lungs, however may gain importance after lung lavage where the airway closures may lead to trapped air in the lung periphery. Using a similar experimental model where the regional lung ventilation was assessed by synchrotron imaging, we recently demonstrated that air trapping may be encountered at PEEP level of 3 cmH 2 O [17]. Considering that the maximum amount of such lung regions with trapped air does not exceed 10%, the impact of this phenomenon on our results is minor.…”
Section: Discussionmentioning
confidence: 94%
“…The pathogenesis of this severe pulmonary disorder is far more complex then the loss of surfactant function. Nonetheless, the present model mimics lung collapsibility and the loss or regional lung ventilation with increased heterogeneity, particularly at low PEEP levels [17]. Atelectasis development was evidenced from the marked and significant decreases in EELV MBW,He (-38 ± 5.3%, p < 0.005) and ELV (-65 ± 4.2%, p < 0.001) at PEEP 0.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Instead, the radiologic pattern may be of diffusely distributed moderately aerated tissue 6 . Though the volume of aerated lung may be appreciable in diffuse injury 7 , aerated and non-aerated lung are co-localized such that lung tissue interdependence 8,9 may be important. It is unlikely that the same relationship among inflation, deformation, and injury is at play when a given V T inflates a separate aerated lung compartment, compared with where aeration and non-aeration are diffusely intermingled.…”
Section: Introductionmentioning
confidence: 99%